2021
DOI: 10.3390/biomedicines9101424
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Nerve Abnormalities in Painful Dry Eye Disease Patients

Abstract: This study aimed to compare the corneal nerve structural abnormalities detected using in vivo confocal microscopy (IVCM) in patients with neuropathic corneal pain (NCP) secondary to primary meibomian gland dysfunction (MGD) or autoimmune dry eye (AIDE). Methods: A two-stage retrospective nested case–control study was conducted. First, data from patients with either MGD or AIDE were assessed, selecting only cases with no corneal pain (VAS = 0) or severe pain (VAS ≥ 8). Ocular signs and symptoms of the 238 selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…First, although the OSDI and SPEED questionnaires are validated and widely used instruments to evaluate dry eye, they may not accurately identify the DED symptoms of patients with corneal sensation disorders (which might be caused by older age, neurological problems, etc.) (30,(59)(60)(61). Therefore, it is advisable to evaluate a patient's corneal nerve condition using confocal microscopy before assessing the symptoms of DED.…”
Section: Discussionmentioning
confidence: 99%
“…First, although the OSDI and SPEED questionnaires are validated and widely used instruments to evaluate dry eye, they may not accurately identify the DED symptoms of patients with corneal sensation disorders (which might be caused by older age, neurological problems, etc.) (30,(59)(60)(61). Therefore, it is advisable to evaluate a patient's corneal nerve condition using confocal microscopy before assessing the symptoms of DED.…”
Section: Discussionmentioning
confidence: 99%
“…Topical ω-3 (in particular, DHA) might also promote regeneration of the corneal nerve plexus, which is damaged in DED, as demonstrated in Cagini’s study in our review and is borne out elsewhere [ 61 , 62 ]. One explanation is that human corneal epithelial cells express 15-LOX, which converts topical DHA into neuroprotectin D1 (NPD1) [ 63 ], which is understood to be a pro-resolving mediator [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 55%
“…3 A recent study revealed that relying solely on the presence or density of CSENPS is not sufficient to diagnose neuropathic corneal pain, and additional morphological features, including area and perimeter, could be indicative of dry eye-related neuropathic pain. 5 Findings from the present study provide a basis for subsequent investigations into how the density and morphology of CSENPS may be altered in disease, and the potential utility of such features as biomarkers of corneal pathology.…”
mentioning
confidence: 70%